Análise temporal do índice de qualidade da água (iqa) na bacia do rio Jundiaí e o impacto da pandemia de covid-19 no monitoramento de sistemas hídricos - Rocha, Caio; Mânica, Alana Natalí; Gomes, Renata Suzi; Isaac, Ricardo de Lima (International Workshop for Innovation in Safe Drinking Water, 2022)
The water quality index (WQI) is a tool based on some physical, chemical and biological parameters, to directly qualify water in a single indexed value. The Jundiai River Basin, located in São Paulo State/Brazil, is an urbanized watershed and suffers from historical problems related to the quality of its water resources. This study aimed to analyze the WQI from 11 monitoring points along the Jundiai River Basin in two different periods (2010/2011) and (2020/2021). Secondary temporal data of water quality parameters were collected and the computed indexes were spatially interpolated. As results, improvements in water quality were observed in 4 sampling points, all of them located in the Jundiai River. Two, and two other sampling points, tributaries of the Jundiai River, has reduced in WQI category. The SARS-CoV-2 pandemic had a negative impact on field data collect for WQI measurement in Jundiai River Basin. This may affect the accuracy of WQI values for the period 2020/2021.